Conocimientos sobre hipertensión arterial y prácticas de autocuidado en pacientes integrantes del Club de Hipertensos Juntos por la Vida del Hospital Universitario de Motupe - Cueva Rodríguez, Cecilia Beatriz (2013)
The present study "Knowledge on hypertension and self-care practices in patients with hypertension club members" Together Through Life "was performed at the University Hospital of Motupe, applying as structural survey instrument that included questions on basic knowledge about the disease and self-care practices that help them cope with the disease and delay complications. Among the results obtained in the investigation included the following: most people are female between 45-65 years old. The entire club members have knowledge about hypertension, risk factors, treatment and frequent complications. Regarding self-care practices that apply patient members excelled in their daily lives: food, exercise, medical checks and taking medication, but many of them drink coffee, do not control your blood pressure daily and neither do EKG control. Keywords: Hypertension, level of knowledge, self-care practices.